Adalimumab for maintenance therapy for one year in Crohn's disease: results of a Latin American single-center observational study - Kotze, Paulo Gustavo; Abou-Rejaile, Vinícius Rezende; Uiema, Luciana Aparecida; Olandoski, Marcia; Sartor, Maria Cristina; Miranda, Eron Fábio; Kotze, Lorete Maria da Silva; Saad-Hossne, Rogério [UNESP] (FapUNIFESP (SciELO), 2014)
Adalimumab is a fully-human antibody that inhibits TNF alpha, with a significant efficacy for long-term maintenance of remission. Studies with this agent in Latin American Crohn's disease patients are scarce. The objective of this study was to outline clinical remission rates after 12 months of adalimumab therapy for Crohn's disease patients. Retrospective, single-center, observational study of a Brazilian case series of Crohn's disease patients under adalimumab therapy. Variables analyzed: demographic data, Montreal classification, concomitant medication, remission rates after 1, 4, 6 and 12 months. Remission was defined as Harvey-Bradshaw Index ≤ 4, and non-responder-imputation and last-observation-carried-forward analysis were used. The influence of infliximab on remission rates was analyzed by Fischer and Chi-square tests (P<0.05). Fifty patients, with median age of 35 years at therapy initiation, were included. Remission rates after 12 months of therapy were 54% under non-responder-imputation and 88% under last-observation-carried-forward analysis. After 12 months, remission on patients with previous infliximab occurred in 69.23% as compared to 94.59% in infliximab-naïve patients (P = 0.033). Adalimumab was effective in maintaining clinical remission after 12 months of therapy, with an adequate safety profile, and was also more effective in infliximab naïve patients.
Adalimumabe na terapia de manutenção por um ano na doença de Crohn: resultados de um estudo observacional unicêntrico Latinoamericano
Keywords: Tumor necrosis factor-alpha; Adrenergic alpha-antagonists, administration and dosage; Crohn disease, prevention and control.